Cost-effectiveness of personalized supplementation with vitamin D-rich dairy products in the prevention of osteoporotic fractures. Issue 1 (January 2016) - Ethgen, O.; Hiligsmann, M.; Burlet, N.; Reginster, J.-Y.
Abstract Summary Titrated supplementations with vitamin D-fortified yogurt, based on spontaneous calcium and vitamin D intakes, can be cost-effective in postmenopausal women with or without increased risk of osteoporotic fractures. Introduction The objective of this study is to assess the cost-effectiveness of the vitamin D-fortified yogurt given to women with and without an increased risk of osteoporotic fracture. Methods A validated cost-effectiveness microsimulation Markov model of osteoporosis management was used. Three personalized supplementation scenarios to reflect the Ca/Vit D needs taking into account the well-known variations in dietary habits and a possible pharmacological supplementation in Ca/Vit D, given above or in combination with anti-osteoporosis medications: one yogurt per day, i.e., 400 mg of Ca + 200 IU of Vit D (scenario 1 U), two yogurts per day, i.e., 800 mg of Ca + 400 IU of Vit D (scenario 2 U), or three yogurts per day, i.e., 1, 200 mg of Ca + 600 IU of Vit D (scenario 3 U). Results One yogurt is cost-effective in the general population above the age of 70 years and in all age groups in women with low bone mineral density (BMD) or prevalent vertebral fracture (PVF). The daily intake of two yogurts is cost-effective above 80 years in the general population and above 70 years in the two groups of women at increased risk of fractures. However, an intake of three yogurts per day is only cost-effective above 80 years old in the general population, as well as in women with low BMD or PVF. Conclusions Our study is the first economic analysis supporting the cost-effectiveness of dairy products, fortified with vitamin D, in the armamentarium against osteoporotic fractures.